The Impact of Corporate Social Responsibility, Investment Opportunity Set, and Capital Structure on Firm Value: The Role of Good Corporate Governance as a Moderating Variable - Zahra, Tiara Aulia; Suryadi, Nanda; Deli, Mazzlida Mat; Utariani, Ni Ketut Raka (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2024)
This study was conducted with the aim of providing empirical evidence of the influence of Corporate Social Responsibility, Investment Opportunity Set, and Capital Structure on Firm Value with Good Corporate Governance as a moderating variable in SOEs listed on the IDX for the 2018-2022 period. The population of this study is state-owned companies listed on the Indonesia Stock Exchange in 2018-2022. The sampling technique used is using the purpose sampling method, where samples are taken through various criteria determined by the researcher. So that the number of samples in this study amounted to 14 companies out of 24 existing companies. The hypothesis in this study is tested through the Outer Model and Inner Model with the help of SmartPLS v 3.0 software. The conclusion of this study is that Corporate Social Responsibility and Capital Structure have no effect on Firm Value, while Investment Opportunity Set has an effect on Firm Value. In addition, Good Corporate Governance is able to strengthen the relationship between Corporate Social Responsibility and Capital Structure to Firm Value, and Good Corporate Governance is unable to strengthen the relationship between Investment Opportunity Set and Firm Value